CarbX: a program for the evaluation of wide‐angle X‐ray scattering data of non‐graphitic carbons. Issue 1 (30th January 2018) - Pfaff, Torben; Simmermacher, Mats; Smarsly, Bernd M.
Abstract : The program CarbX for the analysis of non‐graphitic carbons is presented. Abstract : CarbX is an open‐source program designed for the analysis of wide‐angle X‐ray scattering (WAXS) data of non‐graphitic carbons (NGCs). As knowledge of their microstructure is crucial for tuning desired properties, an `easy‐to‐use' analysis tool is essential for effective research in this field. Using CarbX one can retrieve up to 14 microstructural parameters from a single WAXS pattern without having to master the associated complicated mathematics. CarbX was developed to serve as a convenient graphical user interface, translating a complex evaluation algorithm introduced by Ruland & Smarsly [ J. Appl. Cryst. (2002), 35, 624–633] into software which can be operated by non‐experts. Besides the core functionality of displaying data and manually fitting WAXS curves by user‐editable parameters, CarbX offers additional features such as visualization of the deviation between data and fit, the possibility to choose the wavelength used in the measurement, and automatic fitting (using Wolfram Mathematica ). One of the key features of the comfortable usability is the functionality to display templates. This allows the user to visually compare measurement data with typical types of NGC WAXS curves which are presented graphically around the measurement data. The authors believe that this program will provide a useful tool for scientists dealing with the characterization of NGCs.